Editing - Chang, Justin (Focal Press, 2012)
"Through seventeen exclusive interviews with some of the world's top film editors, this book explores the art of film editing; its complex processes, the relationship with other film practitioners, and the impact of developments in modern editing techniques."--Zadní s. obálky
Terminologický slovník
Obsahuje rejstřík
Keywords: filmová výroba; střihová skladba; filmová tvorba; filmoví umělci; film production industry; film editing; art of film production; film artists; rozhovory; interviews